Corrosion-resistant treatment method for high-speed rail sound barrier
Through the use of modified scale zinc powder and modified graphene and other materials, corrosion-resistant sealing paste, sealant and sealant were prepared, which solved the corrosion problems caused by the gap after the anti-corrosion treatment of the high-speed iron acoustic barrier connecting bolt structure, achieved more efficient corrosion resistance and sealing performance, and met the requirements of long-term corrosion protection.
Patent Information
- Application Number
- CN202411840181.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-28
AI Technical Summary
The connecting bolt structure of the existing high-speed rail acoustic barrier is prone to gaps after anti-corrosion treatment, resulting in invasion of corrosive media. The existing technology is difficult to meet the 50-year long-term anti-corrosion technical requirements.
Corrosion-resistant sealing paste, sealant and sealant are prepared by modified flake zinc powder and modified graphene. Through the modification and combination of these materials, the corrosion resistance and sealing performance of the materials are improved.
It effectively fills the gap between the connecting bolt structure in the acoustic barrier, improves the overall physical and mechanical properties of the material and corrosion resistance, and meets the needs of long-term corrosion protection.
Smart Images

Figure CN119529733A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrosion-resistant polymer materials and relates to a corrosion-resistant treatment method for a high-speed railway sound barrier. Background Art
[0002] Sound barriers are widely used in high-speed railway construction as an important measure to reduce noise pollution. Therefore, the structural safety of high-speed railway sound barriers is very important. There are many connecting bolt structures in the sound barriers. Corrosion of these structures will cause serious safety hazards.
[0003] At present, the anti-corrosion of sound barrier columns mainly adopts hot-dip galvanizing technology, while the embedded anchor bolts, steel plates and unit plate mounting bolts adopt multi-element co-penetration anti-corrosion technology.
[0004] The traditional connecting bolt structure is pre-buried on the roadbed base after anti-corrosion treatment or added later, and fixed to the existing concrete foundation with expansion bolts. However, in this treatment, since the support base plate is processed with bolt holes, the support and base plate are directly placed on the embedded bolts after anti-corrosion treatment, and positioning nuts for up and down adjustment are added under some base plates. In this way, there will inevitably be a gap between the support base plate and the concrete base, resulting in the invasion of corrosive media. Therefore, the prior art uses traditional sealants to seal the exposed bolts between the support base plate and the base concrete, which improves the anti-corrosion performance, but it is difficult to perform daily maintenance on the bolts after they are wrapped with sealants. There are many factors affecting the corrosion of the connection parts, and the existing technology is insufficient in anti-corrosion ability, making it difficult to meet the 50-year long-term anti-corrosion technical requirements.
[0005] In response to the above problems, a new corrosion-resistant treatment system is needed to maintain the necessary corrosion resistance of high-speed rail sound barriers. Summary of the invention
[0006] The purpose of the present invention is to provide a corrosion resistance treatment method for high-speed railway sound barriers. Through the method of the present invention, the corrosion resistance of high-speed railway sound barriers can be optimized.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A corrosion-resistant treatment method for a high-speed railway sound barrier comprises the following steps:
[0009] S1. Preparation of modified flake zinc powder:
[0010] S1.1. Replace the gas in the ball mill with nitrogen for 3 times, first add toluene 10 to 20 times the volume of the flake zinc powder, then add the flake zinc powder, first stir at a low speed of 100 to 150 r / min for 5 to 10 minutes, after pre-dispersion, maintain the speed at 200 to 500 r / min and the temperature at 30 to 40°C, perform ball milling for 4 to 12 hours, disperse the flake zinc powder evenly, then add a dehumidifier of 3 to 10% by mass of the flake zinc powder, maintain the ball milling dispersion conditions and continue the ball milling treatment for 1 to 4 hours; then add an adhesion promoter of 3 to 10% by mass of the flake zinc powder, maintain the conditions for ball milling treatment for 1 to 4 hours, and freeze-dry at -60 to -80°C for 40 hours to obtain the pretreated flake zinc powder;
[0011] S1.2, using a new clean and dry ball mill and replacing the air with clean nitrogen, add 5 to 10 times the volume of the pre-treated flake zinc powder toluene solvent, then add 5 to 10% of the mass of the toluene solution of polyamide wax powder, stir at a low speed of 100 to 150 r / min until the polyamide wax powder is completely dissolved, then add the pre-treated flake zinc powder, the temperature is 30 to 40 ° C, the speed of 200 to 500 r / min ball milling treatment for 2 to 3 hours, and freeze-dry at -60 to -80 ° C for 40 hours to obtain the modified flake zinc powder;
[0012] S2. Preparation of modified graphene:
[0013] S2.1, add ethyl acetate solution with a total volume of 300-500% of the volume of graphene into the reactor, then add a dehumidifier accounting for 1-2% of the mass of graphene, add graphene after mixing evenly, stir at a low speed of 100-150r / min for 5-30min, then stir and reflux at 50-60°C for 4-6h, cool naturally to room temperature after stirring, and freeze-dry at -60--80°C for 24-40h to obtain pretreated graphene;
[0014] S2.2, under nitrogen protection, acrylamide and methacryloyloxyethyl trimethyl ammonium chloride, 4-chloromethyl styrene and ammonium persulfate in a molar ratio of 10:3:0.02:0.005 are mixed, the temperature is raised to 55-65°C, and stirred for 10-14 hours. After the stirring is completed, anhydrous ethanol is added for extraction, and freeze-dried at -60--80°C for 24 hours to obtain a cationic polyacrylamide prepolymer;
[0015] S2.3, adding cationic polyacrylamide prepolymer and enzymatic lignin in a mass ratio of (1-3):1 to a sodium hydroxide solution with a concentration of 1 mol / L, stirring at 60-80°C for 5 h, cooling to room temperature after stirring, extracting with acetone, discarding the upper liquid, filtering the remaining solid product, concentrating, and freeze-drying at -60°C for 24 h to obtain pure lignin-based cationic polyacrylamide;
[0016] S2.4, 40 to 60 parts of a 1 to 1.5 g / L lignin-based cationic polyacrylamide aqueous solution and 15 to 25 parts of pretreated graphene are uniformly mixed, spray-dried at 60 to 90° C., and then ground in a ball mill at a speed of 350 r / min for 4 h to prepare the modified graphene;
[0017] S3, preparing corrosion-inhibiting sealing paste, corrosion-inhibiting sealant and corrosion-inhibiting sealant;
[0018] S4. Pretreatment of high-speed rail sound barrier:
[0019] Before installing the high-speed rail sound barrier, clean the upper surface of the embedded parts and the surrounding concrete surface, bolts and exposed surfaces, and then apply special primer to protect the substrate from waterproofing and seepage;
[0020] S5, corrosion-inhibiting sealing paste treatment:
[0021] Apply corrosion-inhibiting sealant between the support base plate and the base concrete, on the bolts, the surface of the support screw holes, and the inner surface of the nuts, fix the bolts in the support screw holes, then screw on the nuts and place the support to ensure that the space between the support base plate and the base concrete is filled with corrosion-inhibiting sealant so that there is no gap between the support base plate and the base concrete;
[0022] S6, corrosion-inhibiting sealant treatment:
[0023] Tighten the nuts of the connecting bolts to the required standard, remove the corrosion-inhibiting sealant remaining on the edge of the joints between the exposed bolts, the support base plate and the concrete foundation, and then apply a layer of corrosion-inhibiting sealant on the surface of the exposed bolts;
[0024] S7, corrosion-inhibiting sealant treatment:
[0025] A layer of corrosion-inhibiting sealant is scraped on the edge of the joint between the base plate and the concrete of the foundation to ensure a smooth slope at the joint. After it is completely dried, a corrosion-resistant high-speed rail sound barrier will be obtained.
[0026] As a preferred technical solution of the present invention, in step S1 and step S2, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21.
[0027] As a preferred technical solution of the present invention, in step S1, the adhesion promoter is one of Meitu A-1120 and domestic WD51.
[0028] As a preferred technical solution of the present invention, in step S3, the preparation process of the corrosion-inhibiting sealing paste is as follows:
[0029] S4.1. First, wash the double planetary stirring kettle with deionized water, dry it at 100-105°C for 8-12h, and then introduce nitrogen for 50-80min. Then, add 20-40 parts of MS S327-silane modified polyether resin, 10-28 parts of non-alcoholic plasticizer, 5-10 parts of hydrophobic fumed silica and 0-20 parts of nano calcium carbonate in the stirring kettle in order by weight, and then stir for 45-60min, wherein the stirring temperature is 90-110°C, the vacuum degree is -0.09--0.1MPa, and the stirring speed is 800-1000r / min.
[0030] S4.2. Cool the material temperature in the double planetary stirred tank to below 40°C, add 1 to 2 parts of dehumidifier, stir at a speed of 500 to 600 r / min for 10 to 20 min, add 1 to 2 parts of adhesion promoter, stir at a speed of 400 to 600 r / min for 10 to 20 min, then add 15 to 30 parts of flake zinc powder, stir at a vacuum degree of -0.09 to -0.1 MPa and a stirring speed of 600 to 800 r / min for 20 to 45 min, then add 10 to 15 parts of modified flake zinc powder, keep stirring for 15 to 30 min while keeping the conditions unchanged;
[0031] S4.3. Finally, clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and then the material is discharged and sealed to obtain the corrosion-inhibiting sealing paste.
[0032] As a preferred technical solution of the present invention, in step S3, the preparation process of the corrosion-inhibiting sealant is as follows:
[0033] S5.1. First wash the double planetary stirring kettle with deionized water, then dry it at 100-105℃ for 8-12h, and then fill it with clean dry nitrogen to replace the air in the double planetary stirring kettle 2-3 times;
[0034] S5.2, add 20-30 parts of α-dimethoxysilane-terminated polyether resin, 10-20 parts of γ-trimethoxysilane-terminated polyether resin, 15-20 parts of non-alcohol plasticizer, 8-20 parts of hydrophobic fumed silica, 1-2 parts of carbon black, 5-30 parts of nano calcium carbonate in a double planetary stirred kettle, and then stir for 30-60 minutes, wherein the stirring temperature is 90-110°C, the vacuum degree is -0.09-0.1MPa, and the stirring speed is 800-1000r / min;
[0035] S5.3. Cool the material temperature in the double planetary stirred tank to below 40°C, first add 1 to 2 parts of dehumidifier, stir at a speed of 300 to 500 r / min for 5 to 10 minutes, continue to add 1 to 5 parts of modified graphene and 5 to 10 parts of modified flake zinc powder, stir for 10 to 30 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min; then add 1 to 2 parts of adhesion promoter, stir at a speed of 300 to 500 r / min for 5 to 10 minutes, then add 1 to 2 parts of catalyst, stir for 5 to 10 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min;
[0036] S5.4. Use clean dry nitrogen to adjust the double planetary stirring kettle to normal pressure, and finally discharge the materials and seal them to prepare the corrosion-inhibiting sealant.
[0037] As a preferred technical solution of the present invention, in step S3, the preparation process of the corrosion-inhibiting sealant is as follows:
[0038] S6.1. First wash the double planetary stirring kettle with deionized water, then dry it at 100-105°C for 8-12 hours, and then fill it with clean dry nitrogen to replace the air in the double planetary stirring kettle 2-3 times;
[0039] S6.2, add 20-30 parts of silane-modified polymer resin, 10-20 parts of non-alcohol plasticizer, 35-50 parts of nano calcium carbonate, 1-2 parts of carbon black, 0.5-2 parts of hydrophobic fumed silica into a double planetary stirred kettle, and then stir for 60-90 minutes, wherein the stirring temperature is 90-110°C, the vacuum degree is -0.09-0.1MPa, and the stirring speed is 800-1000r / min;
[0040] S6.3. Cool the material temperature in the double planetary stirred tank to below 40°C, first add 1 to 2 parts of dehumidifier, disperse at a speed of 500 to 800 r / min for 10 to 20 minutes, then add 2 to 5 parts of flake zinc powder, 1 to 5 parts of modified graphene, and 2 to 5 parts of modified flake zinc powder, and stir for 30 to 60 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min; then add 1 to 2 parts of adhesion promoter, stir at a speed of 800 to 1000 r / min for 10 to 20 minutes, then add 1 to 2 parts of catalyst, and stir for 20 to 30 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min;
[0041] S6.4. Use clean dry nitrogen to adjust the double planetary stirring kettle to normal pressure, and finally discharge the materials and seal them to prepare the corrosion-inhibiting sealant.
[0042] As a preferred technical solution of the present invention, in step S4.1, the non-alcohol plasticizer is one of diisononyl phthalate, dioctyl phthalate and diisodecyl phthalate; in step S4.2, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21, and the adhesion promoter is one of Meitu A-1120 and domestic WD51.
[0043] As a preferred technical solution of the present invention, in step S5.2, the non-alcohol plasticizer is one of diisononyl phthalate, dioctyl phthalate and diisodecyl phthalate; in step S5.3, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21, the adhesion promoter is one of Meitu A-1120 and domestic WD51, and the catalyst is one of stannous octoate and dibutyltin dilaurate.
[0044] As a preferred technical solution of the present invention, in step S6.2, the non-alcohol plasticizer is one of diisononyl phthalate, dioctyl phthalate and diisodecyl phthalate; in step S6.3, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21, and the adhesion promoter is one of Meitu A-1120 and domestic WD51.
[0045] As a preferred technical solution of the present invention, in step S6.3, the catalyst is one of stannous octoate and dibutyltin dilaurate.
[0046] Beneficial effects of the present invention:
[0047] (1) In the present invention, the flake zinc powder is modified, and the flake zinc powder is first pretreated by coupling the dehumidifier, adhesion promoter and the flake zinc powder, and then the polyamide wax is used for coating and protection. Through this modification, on the one hand, the polyamide wax can delay the time for the flake zinc powder to play a role, and on the other hand, the polyamide wax coating layer on the surface of the flake zinc powder has a certain brittleness, and it is easy to break when it is subjected to external force, and the pretreated flake zinc powder can be released. At this time, the dehumidifier coupled to the surface of the pretreated flake zinc powder will quickly eliminate the moisture invading the damaged part, and at the same time, the adhesion promoter ensures that the flake zinc powder at the damaged part is firmly attached and exerts its sacrificial protection of the anode metal, so as to achieve a more efficient corrosion resistance, and at the same time, it is also conducive to the self-repair of the sealing layer at the damaged part, and further improves the corrosion resistance. Polyamide wax can also be used as a rheological additive. It can improve the rheological properties of the material and increase the viscosity of the system, thereby achieving the effect of anti-settling and anti-sagging.
[0048] In the present invention, a dehumidifier is used to perform a special silane coupling treatment on the surface of graphene particles, which can ensure that the graphene powder is dispersed while optimizing its compatibility and dispersibility with the corrosion-inhibiting sealant system, thereby improving the improvement effect of graphene on the performance of the corrosion-inhibiting sealant coating. After pretreatment, the graphene is modified with lignin-based cationic polyacrylamide, which has cationic properties and can electrostatically adsorb anionic compounds, thereby enhancing the adsorption capacity of the modified graphene for corrosive media. This adsorption performance helps to reduce the penetration and diffusion of corrosive media in the sealant, and improves the corrosion resistance of the sealant and sealant. At the same time, lignin-based cationic polyacrylamide, as a high molecular surfactant, can effectively wrap around the graphene surface, enhance the dispersibility and stability of graphene in sealing materials, prevent graphene agglomeration and precipitation, and enable graphene to maintain a uniform dispersion state in various applications, thereby giving full play to its performance. Its wrapping layer can serve as an interface layer between graphene and the matrix, enhance the interaction and compatibility between graphene and the matrix, and as a physical barrier, it can block the erosion of corrosive media and improve corrosion resistance.
[0049] (2) In the present invention, modified graphene and modified flake zinc powder are added to the prepared corrosion-inhibiting sealing paste, corrosion-inhibiting sealant and corrosion-inhibiting sealant, and the modified graphene and modified flake zinc powder are added to the raw materials in advance during the preparation process, which is conducive to the subsequent dispersion and ensures uniform dispersion. Among them, the modified graphene helps to improve the compatibility and dispersibility of each component in the corrosion-inhibiting sealant and the corrosion-inhibiting sealant, and the modified flake zinc powder can effectively deal with the problem that the damaged part of the sealing material is easily corroded by corrosive media after being damaged by external force. The three prepared sealing materials improve the overall physical and mechanical properties and corrosion resistance of the materials.
[0050] (3) When the corrosion-inhibiting sealing paste, corrosion-inhibiting sealant and corrosion-inhibiting sealant prepared by the present invention are used for corrosion-resistant treatment of high-speed rail sound barriers, the corrosion-inhibiting sealing paste fills the internal gaps of the connecting structure, the corrosion-inhibiting sealant is brushed to protect the bolts and nuts, and the corrosion-inhibiting sealant is scraped to strengthen the gap between the support base plate and the base concrete. When the internal fasteners of the screws are worn, the corrosion-inhibiting sealing paste can infiltrate and protect them in time. If corrosive media invade, its corrosion-resistant anti-corrosion additive can effectively play a role; the corrosion-inhibiting sealant can reduce the damage to the nut itself by virtue of its own tensile strain, toughness and self-repairing effect; the corrosion-inhibiting sealant layer has excellent tensile strength and elongation, etc., which can resist the displacement changes of the bolted structure caused by external forces (such as vibration, impact), ensure the reliability of sealing and corrosion protection, and thus achieve effective corrosion protection for the high-speed rail sound barrier. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0052] Figure 1 It is a schematic diagram of the application structure of the present invention. DETAILED DESCRIPTION
[0053] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0054] In the following embodiments:
[0055] In the present invention, freeze drying is performed by a vacuum freeze dryer, the temperature of the vacuum freeze dryer is -56±4°C, and the time is 20h;
[0056] The polyamide wax is Lubrizol Lanco A1601; the silane-modified polymer resin is MS S303H; the dehumidifier is Maitu A-171; the adhesion promoter is Meitu A-1120; the catalyst is stannous octoate. Acrylamide: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., product number: A800656; methacryloyloxyethyl trimethylammonium chloride: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., product number: M812868; 4-chloromethylstyrene: purchased from Shandong Xingshun New Materials Co., Ltd.; enzymatic lignin: purchased from Wuhan Jiyesheng Chemical Co., Ltd., product number: A01095.
[0057] The following examples are all prepared by corrosion-inhibiting sealing paste, corrosion-inhibiting sealant and corrosion-inhibiting sealant, and then used for corrosion-resistant treatment of high-speed rail sound barriers, and the process is as follows:
[0058] High-speed rail sound barrier pretreatment:
[0059] Before installation, clean the upper surface of the embedded parts and the surrounding concrete surface, bolts and exposed surfaces, and then apply special primer to protect the substrate from waterproofing and seepage;
[0060] Corrosion-inhibiting sealant treatment:
[0061] Apply corrosion-inhibiting sealant between the support base plate and the base concrete, on the bolts, the surface of the support screw holes, and the inner surface of the nuts, fix the bolts in the support screw holes, then screw on the nuts and place the support to ensure that the space between the support base plate and the base concrete is filled with corrosion-inhibiting sealant so that there is no gap between the support base plate and the base concrete;
[0062] Corrosion Inhibiting Sealant Treatment:
[0063] Tighten the nuts of the connecting bolts to the required standard, remove the corrosion-inhibiting sealant remaining on the edge of the joints between the exposed bolts, the support base plate and the concrete foundation, and then apply a layer of corrosion-inhibiting sealant on the surface of the exposed bolts;
[0064] Corrosion Inhibiting Sealant Treatment:
[0065] A layer of corrosion-inhibiting sealant is scraped on the edge of the joint between the base plate and the concrete of the foundation to ensure a smooth slope at the joint. After it is completely dried, a corrosion-resistant high-speed rail sound barrier will be obtained.
[0066] 1. Preparation of corrosion-inhibiting sealing paste:
[0067] The weight parts of each raw material component in Examples 1-3 are shown in Table 1:
[0068] Table 1
[0069]
[0070]
[0071] Example 1
[0072] Preparation of modified flake zinc powder:
[0073] The ball mill was gas-replaced with nitrogen for 3 times, and toluene was first added in an amount 10 times the volume of the flake zinc powder, and then the flake zinc powder was added, and the mixture was stirred at a low speed of 100 r / min for 5 min. After pre-dispersion, the rotation speed was maintained at 200 r / min and the temperature was maintained at 30° C., and the flake zinc powder was ball-milled for 4 h to disperse the flake zinc powder uniformly, and then a dehumidifier of 3% by mass of the flake zinc powder was added, and the ball milling dispersion conditions were maintained to continue the ball milling treatment for 1 h; an adhesion promoter of 3% by mass of the flake zinc powder was then added, and the conditions were maintained for ball milling treatment for 1 h, and the pre-treated flake zinc powder was obtained by freeze-drying;
[0074] A new clean and dry ball mill is used and the air is replaced with clean nitrogen. Then, a toluene solvent of 5 times the volume of the pretreated flake zinc powder is added, and then a polyamide wax powder accounting for 5% of the mass of the toluene solution is added. The mixture is stirred at a low speed of 100 r / min until the polyamide wax powder is completely dissolved. Then, the pretreated flake zinc powder is added, the temperature is 30° C., and the ball milling is performed at a speed of 200 r / min for 2 hours. The modified flake zinc powder is obtained by freeze-drying.
[0075] The double planetary stirred kettle was first washed with deionized water, then dried at 100°C for 8h, and then nitrogen was introduced for 50min. MS S327-silane-modified polyether resin, non-alcoholic plasticizer (diisodecyl phthalate), hydrophobic fumed silica and nano-calcium carbonate were added to the stirred kettle in sequence according to the weight parts in Table 1, and then stirred for 45min, wherein the stirring temperature was 90°C, the vacuum degree was -0.09MPa, and the stirring speed was 800r / min;
[0076] The material temperature in the double planetary stirring kettle was cooled to below 40°C, and then a dehumidifier was added, and the mixture was stirred at a speed of 500 r / min for 10 min. Then, an adhesion promoter was added, and the mixture was stirred at a speed of 400 r / min for 10 min. Then, flake zinc powder was added, and the mixture was stirred at a vacuum degree of -0.09 MPa and a stirring speed of 600 r / min for 20 min. Then, the modified flake zinc powder was added, and the stirring was continued for 15 min while maintaining the same conditions.
[0077] Finally, clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and then the materials are discharged and sealed to obtain the corrosion-inhibiting sealing paste.
[0078] Example 2
[0079] Preparation of modified flake zinc powder:
[0080] The ball mill was gas-replaced with nitrogen for 3 times, and toluene was first added in an amount 15 times the volume of the flake zinc powder, and then the flake zinc powder was added, and the mixture was stirred at a low speed of 130 r / min for 7 minutes. After pre-dispersion, the rotation speed was maintained at 300 r / min and the temperature was maintained at 35°C, and the flake zinc powder was ball-milled for 8 hours to disperse the flake zinc powder uniformly, and then a dehumidifier was added in an amount of 7% by mass of the flake zinc powder, and the ball milling dispersion conditions were maintained to continue the ball milling treatment for 3 hours; an adhesion promoter was then added in an amount of 6% by mass of the flake zinc powder, and the conditions were maintained for ball milling treatment for 3 hours, and the pre-treated flake zinc powder was obtained by freeze-drying;
[0081] A new clean and dry ball mill is used and the air is replaced with clean nitrogen. Then, 8 times the volume of the pretreated flake zinc powder is added toluene solvent, and then 7% of the mass of the toluene solution is added. The mixture is stirred at a low speed of 130 r / min until the polyamide wax powder is completely dissolved. Then, the pretreated flake zinc powder is added, the temperature is 35° C., and the ball milling is carried out at a speed of 300 r / min for 2.5 hours. The modified flake zinc powder is obtained by freeze-drying.
[0082] The double planetary stirring kettle was first washed with deionized water, then dried at 103°C for 10h, and then nitrogen was introduced for 60min. MS S327-silane-modified polyether resin, non-alcoholic plasticizer (diisodecyl phthalate), hydrophobic fumed silica and nano-calcium carbonate were added to the stirring kettle in order according to the weight parts in Table 1, and then stirred for 50min, wherein the stirring temperature was 100°C, the vacuum degree was -0.09MPa, and the stirring speed was 900r / min;
[0083] The material temperature in the double planetary stirring kettle was cooled to below 40°C, and then a dehumidifier was added, and the mixture was stirred at a speed of 550 r / min for 15 min. Then, an adhesion promoter was added, and the mixture was stirred at a speed of 500 r / min for 15 min. Then, flake zinc powder was added, and the mixture was stirred at a vacuum degree of -0.09 MPa and a stirring speed of 700 r / min for 35 min. Then, the modified flake zinc powder was added, and the stirring was continued for 20 min while maintaining the same conditions.
[0084] Finally, clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and then the materials are discharged and sealed to obtain the corrosion-inhibiting sealing paste.
[0085] Example 3
[0086] Preparation of modified flake zinc powder:
[0087] The ball mill was gas-replaced with nitrogen for 3 times, and toluene was first added in an amount 20 times the volume of the flake zinc powder, and then the flake zinc powder was added, and the mixture was stirred at a low speed of 150 r / min for 10 min. After pre-dispersion, the rotation speed was maintained at 500 r / min and the temperature was maintained at 40°C, and the flake zinc powder was ball-milled for 12 h to disperse the flake zinc powder evenly, and then a dehumidifier was added in an amount of 10% by mass of the flake zinc powder, and the ball milling dispersion conditions were maintained to continue the ball milling treatment for 4 h; an adhesion promoter was then added in an amount of 10% by mass of the flake zinc powder, and the conditions were maintained for ball milling treatment for 4 h, and the pre-treated flake zinc powder was obtained by freeze-drying;
[0088] A new clean and dry ball mill is used and the air is replaced with clean nitrogen. Then, a toluene solvent 10 times the volume of the pretreated flake zinc powder is added, and then a polyamide wax powder accounting for 10% of the mass of the toluene solution is added. The mixture is stirred at a low speed of 150 r / min until the polyamide wax powder is completely dissolved. Then, the pretreated flake zinc powder is added, the temperature is 40°C, and the ball milling is carried out at a speed of 500 r / min for 3 hours. The modified flake zinc powder is obtained by freeze-drying.
[0089] The double planetary stirred kettle was first washed with deionized water, then dried at 105°C for 12h, and then nitrogen was introduced for 80min. MS S327-silane-modified polyether resin, non-alcoholic plasticizer (dioctyl phthalate), hydrophobic fumed silica and nano-calcium carbonate were added to the stirred kettle in sequence according to the weight parts in Table 1, and then stirred for 60min, wherein the stirring temperature was 110°C, the vacuum degree was -0.1MPa, and the stirring speed was 1000r / min;
[0090] The material temperature in the double planetary stirring kettle was cooled to below 40°C, and then a dehumidifier was added, and the mixture was stirred at a speed of 600 r / min for 20 min. Then, an adhesion promoter was added, and the mixture was stirred at a speed of 600 r / min for 20 min. Then, flake zinc powder was added, and the mixture was stirred at a vacuum degree of -0.1 MPa and a stirring speed of 800 r / min for 45 min. Then, the modified flake zinc powder was added, and the stirring was continued for 30 min while maintaining the same conditions.
[0091] Finally, clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and then the materials are discharged and sealed to obtain the corrosion-inhibiting sealing paste.
[0092] Performance Test:
[0093] Surface drying time: "Test methods for building sealing materials Part 5: Determination of surface drying time" (GB / T 13477.5-2002);
[0094] pH value: "Determination of pH value of adhesives" (GB / T 14518-1993);
[0095] Total zinc content and elemental zinc content: tested in accordance with the provisions of "Zinc Powder" (GB / T 6890-2000), and sample preparation is carried out in accordance with the relevant sample preparation method of "Zinc-rich Primer" (HG / T 3668-2020);
[0096] Storage stability: Visual inspection after sampling;
[0097] 1000h salt spray resistance test: Tested in accordance with the provisions of "Artificial atmosphere corrosion test salt spray test" (GB / T10125-2021), and the plate preparation is carried out in accordance with the relevant sample preparation methods in "Technical Conditions for Anti-corrosion Coating of Main Cable Systems of Suspension Bridges" (JT / T 694-2007);
[0098] The performance test results of the corrosion-inhibiting sealant are shown in Table 2:
[0099] Table 2
[0100]
[0101]
[0102] 2. Preparation of corrosion-inhibiting sealant:
[0103] The weight proportions of the raw material components in Examples 4-6 are shown in Table 3, wherein the α-dimethoxysilane-terminated polyether resin is Wacker STP-E10, and the γ-trimethoxysilane-terminated polyether resin is Wacker STP-E15:
[0104] Table 3
[0105]
[0106]
[0107] Example 4
[0108] The process of preparing the modified flake zinc powder is the same as that in Example 1;
[0109] Preparation of modified graphene:
[0110] Add an ethyl acetate solution with a total volume of 300% of the volume of graphene into a reaction kettle, then add a dehumidifier accounting for 1% of the mass of graphene, add graphene after mixing evenly, stir at a low speed of 100 r / min for 5 minutes, then stir and reflux at 50° C. for 4 hours, naturally cool to room temperature after the stirring is completed, and freeze-dry at -60° C. for 40 hours to obtain pretreated graphene;
[0111] Under nitrogen protection, acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, 4-chloromethyl styrene and ammonium persulfate in a molar ratio of 10:3:0.02:0.005 were mixed, the temperature was raised to 55°C, and the mixture was stirred for 10 hours. After the stirring, anhydrous ethanol was added to the product for extraction, and the product was freeze-dried at -60°C for 24 hours to obtain a cationic polyacrylamide prepolymer.
[0112] The cationic polyacrylamide prepolymer and enzymatic lignin in a mass ratio of 1:1 were added to a sodium hydroxide solution with a concentration of 1 mol / L, and stirred at 60°C for 5 hours. After stirring, the mixture was cooled to room temperature, extracted with acetone, and the upper liquid was discarded. The remaining solid product was filtered, concentrated, and freeze-dried at -60°C for 24 hours to obtain pure lignin-based cationic polyacrylamide.
[0113] S2.4, 40 parts of 1 g / L lignin-based cationic polyacrylamide aqueous solution and 15 parts of pretreated graphene were mixed evenly, and the mixture was spray-dried at 60°C to obtain graphene coated with lignin-based cationic polyacrylamide, and the modified graphene was prepared by grinding the mixture in a ball mill at a speed of 350 r / min for 4 h;
[0114] First, wash the double planetary stirred tank with deionized water, dry it at 100°C for 8 hours, and then fill it with clean dry nitrogen to replace the air in the double planetary stirred tank twice;
[0115] In a double planetary stirring kettle, α-dimethoxysilane-terminated polyether resin, γ-trimethoxysilane-terminated polyether resin, non-alcohol plasticizer (diisodecyl phthalate), hydrophobic fumed silica, carbon black, and nano-calcium carbonate were added in sequence, and then stirred for 30 minutes, wherein the stirring temperature was 90° C., the vacuum degree was -0.09 MPa, and the stirring speed was 800 r / min;
[0116] The material temperature in the double planetary stirring kettle was cooled to below 40°C, a dehumidifier was added first, and the mixture was stirred at a speed of 300 r / min for 5 min, and then modified graphene and modified flake zinc powder were added, and the mixture was stirred at a vacuum degree of -0.09 MPa and a speed of 800 r / min for 10 min; then an adhesion promoter was added, and the mixture was stirred at a speed of 300 r / min for 5 min, and then a catalyst was added, and the mixture was stirred at a vacuum degree of -0.09 MPa and a speed of 800 r / min for 5 min;
[0117] Clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and finally the materials are discharged and sealed to prepare the corrosion-inhibiting sealant.
[0118] Example 5
[0119] The process of preparing the modified flake zinc powder is consistent with that in Example 2;
[0120] Preparation of modified graphene:
[0121] Add an ethyl acetate solution with a total volume of 400% of the volume of graphene into a reaction kettle, then add a dehumidifier accounting for 1.5% of the mass of graphene, add graphene after mixing evenly, stir at a low speed of 130 r / min for 20 minutes, then stir and reflux at 55° C. for 5 hours, naturally cool to room temperature after the stirring is completed, and freeze-dry at -70° C. for 30 hours to obtain pretreated graphene;
[0122] Under nitrogen protection, acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, 4-chloromethyl styrene and ammonium persulfate in a molar ratio of 10:3:0.02:0.005 were mixed, the temperature was raised to 60°C, and the mixture was stirred for 12 hours. After the stirring, anhydrous ethanol was added to the product for extraction, and the product was freeze-dried at -70°C for 24 hours to obtain a cationic polyacrylamide prepolymer.
[0123] The cationic polyacrylamide prepolymer and enzymatic lignin in a mass ratio of 1.5:1 were added to a sodium hydroxide solution with a concentration of 1 mol / L, and stirred at 70°C for 5 hours. After stirring, the mixture was cooled to room temperature, extracted with acetone, and the upper liquid was discarded. The remaining solid product was filtered, concentrated, and freeze-dried at -60°C for 24 hours to obtain pure lignin-based cationic polyacrylamide;
[0124] 50 parts of a 1.2 g / L lignin-based cationic polyacrylamide aqueous solution and 20 parts of pretreated graphene were evenly mixed, spray-dried at 70° C., and then ground in a ball mill at a speed of 350 r / min for 4 h to prepare the modified graphene;
[0125] First, wash the double planetary stirred tank with deionized water, dry it at 103℃ for 10h, and then fill it with clean dry nitrogen to replace the air in the double planetary stirred tank twice;
[0126] In a double planetary stirring kettle, α-dimethoxysilane-terminated polyether resin, γ-trimethoxysilane-terminated polyether resin, non-alcohol plasticizer (diisodecyl phthalate), hydrophobic fumed silica, carbon black, and nano-calcium carbonate were added in sequence, and then stirred for 40 minutes, wherein the stirring temperature was 100°C, the vacuum degree was -0.09 MPa, and the stirring speed was 900 r / min;
[0127] The material temperature in the double planetary stirring kettle was cooled to below 40°C, a dehumidifier was added first, and the mixture was stirred at a speed of 400 r / min for 7 min, and then modified graphene and modified flake zinc powder were added, and the mixture was stirred at a vacuum degree of -0.09 MPa and a speed of 900 r / min for 20 min; then an adhesion promoter was added, and the mixture was stirred at a speed of 400 r / min for 7 min, and then a catalyst was added, and the mixture was stirred at a vacuum degree of -0.09 MPa and a speed of 900 r / min for 7 min;
[0128] Clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and finally the materials are discharged and sealed to prepare the corrosion-inhibiting sealant.
[0129] Example 6
[0130] The preparation process of the modified flake zinc powder is consistent with that of Example 3;
[0131] Preparation of modified graphene:
[0132] Add an ethyl acetate solution with a total volume of 500% of the volume of graphene into a reaction kettle, then add a dehumidifier accounting for 2% of the mass of graphene, add graphene after mixing evenly, stir at a low speed of 150r / min for 30min, then stir and reflux at 60°C for 6h, naturally cool to room temperature after stirring, and freeze-dry at -80°C for 24h to obtain pretreated graphene;
[0133] Under nitrogen protection, acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, 4-chloromethyl styrene and ammonium persulfate in a molar ratio of 10:3:0.02:0.005 were mixed, the temperature was raised to 65°C, and the mixture was stirred for 14 hours. After the stirring, anhydrous ethanol was added to the product for extraction, and the product was freeze-dried at -80°C for 24 hours to obtain a cationic polyacrylamide prepolymer.
[0134] The cationic polyacrylamide prepolymer and enzymatic lignin in a mass ratio of 3:1 were added to a sodium hydroxide solution with a concentration of 1 mol / L, and stirred at 80°C for 5 hours. After stirring, the mixture was cooled to room temperature, extracted with acetone, and the upper liquid was discarded. The remaining solid product was filtered, concentrated, and freeze-dried at -60°C for 24 hours to obtain pure lignin-based cationic polyacrylamide.
[0135] 60 parts of 1.5 g / L lignin-based cationic polyacrylamide aqueous solution and 25 parts of pretreated graphene were uniformly mixed, spray-dried at 90° C., and then ground in a ball mill at a speed of 350 r / min for 4 hours to prepare the modified graphene;
[0136] First, wash the double planetary stirred tank with deionized water, dry it at 105°C for 12 h, and then fill it with clean dry nitrogen to replace the air in the double planetary stirred tank three times;
[0137] In a double planetary stirring kettle, α-dimethoxysilane-terminated polyether resin, γ-trimethoxysilane-terminated polyether resin, non-alcohol plasticizer (dioctyl phthalate), hydrophobic fumed silica, carbon black, and nano-calcium carbonate were added in sequence, and then stirred for 60 minutes, wherein the stirring temperature was 110° C., the vacuum degree was -0.1 MPa, and the stirring speed was 1000 r / min;
[0138] The material temperature in the double planetary stirring kettle was cooled to below 40°C, a dehumidifier was added first, and the mixture was stirred at a speed of 500 r / min for 10 min, and then modified graphene and modified flake zinc powder were added, and the mixture was stirred at a vacuum degree of -0.1 MPa and a speed of 1000 r / min for 30 min; then an adhesion promoter was added, and the mixture was stirred at a speed of 500 r / min for 10 min, and then a catalyst was added, and the mixture was stirred at a vacuum degree of -0.1 MPa and a speed of 1000 r / min for 10 min;
[0139] Clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and finally the materials are discharged and sealed to prepare the corrosion-inhibiting sealant.
[0140] According to the relevant test methods specified in the Technical Conditions for Anticorrosion Coating of Main Cable Systems of Suspension Bridges (JT / T 694-2007), the performance test results of the corrosion-inhibiting sealant are shown in Table 4 below:
[0141] Table 4
[0142]
[0143]
[0144] 3. Preparation of corrosion-inhibiting sealant:
[0145] The weight fractions of the raw material components in Examples 7-9 and the performance test data of the corrosion-inhibiting sealants prepared in Examples 7-9 are shown in Table 5:
[0146] The Shore A hardness shall be tested in accordance with the provisions of "Test Method for Indentation Hardness of Vulcanized Rubber or Thermoplastic Rubber Part 1: Shore Durometer Method (Shore Hardness)" (GB / T 531.1-2008); other performance test methods shall be tested in accordance with the relevant provisions of "Technical Conditions for Anti-corrosion Coating of Main Cable System of Suspension Bridge" (JT / T 694-2007).
[0147] Table 5
[0148]
[0149]
[0150] Example 7
[0151] The process of preparing the modified flake zinc powder and the modified graphene is consistent with that in Example 4;
[0152] Preparation of corrosion-inhibiting sealant:
[0153] First, wash the double planetary stirred tank with deionized water, dry it at 100°C for 8 hours, and then fill it with clean dry nitrogen to replace the air in the double planetary stirred tank twice;
[0154] Add silane-modified polymer resin, non-alcohol plasticizer, nano calcium carbonate, carbon black, and hydrophobic fumed silica into a double planetary stirring kettle, and then stir for 60 minutes, wherein the stirring temperature is 90°C, the vacuum degree is -0.09MPa, and the stirring speed is 800r / min;
[0155] The material temperature in the double planetary stirring kettle was cooled to below 40°C, a dehumidifier was added first, and the mixture was dispersed at a speed of 500 r / min for 10 min, and then flake zinc powder, modified graphene, and modified flake zinc powder were added, and the mixture was stirred for 30 min at a vacuum degree of -0.09 MPa and a speed of 800 r / min; then an adhesion promoter was added, and the mixture was stirred at a speed of 800 r / min for 10 min, and then a catalyst was added, and the mixture was stirred for 20 min at a vacuum degree of -0.09 MPa and a speed of 800 r / min;
[0156] Clean dry nitrogen is used to adjust the pressure in the double planetary stirring kettle to normal pressure, and finally the materials are discharged and sealed to prepare the corrosion-inhibiting sealant.
[0157] Example 8
[0158] The process of preparing the modified flake zinc powder and the modified graphene is consistent with that in Example 5;
[0159] Preparation of corrosion-inhibiting sealant:
[0160] First, wash the double planetary stirred tank with deionized water, dry it at 103℃ for 10h, and then fill it with clean dry nitrogen to replace the air in the double planetary stirred tank twice;
[0161] Add silane-modified polymer resin, non-alcohol plasticizer, nano calcium carbonate, carbon black, and hydrophobic fumed silica into a double planetary stirring kettle, and then stir for 70 minutes, wherein the stirring temperature is 100°C, the vacuum degree is -0.09MPa, and the stirring speed is 900r / min;
[0162] The material temperature in the double planetary stirring kettle was cooled to below 40°C, a dehumidifier was added first, and the mixture was dispersed at a speed of 550 r / min for 17 min, and then flake zinc powder, modified graphene, and modified flake zinc powder were added, and the mixture was stirred for 40 min at a vacuum degree of -0.09 MPa and a speed of 850 r / min; then an adhesion promoter was added, and the mixture was stirred at a speed of 900 r / min for 15 min, and then a catalyst was added, and the mixture was stirred for 24 min at a vacuum degree of -0.09 MPa and a speed of 900 r / min;
[0163] Clean dry nitrogen is used to adjust the pressure in the double planetary stirring kettle to normal pressure, and finally the materials are discharged and sealed to prepare the corrosion-inhibiting sealant.
[0164] Example 9
[0165] The process of preparing the modified flake zinc powder and the modified graphene is consistent with that in Example 6;
[0166] An ethyl acetate solution with a total volume of 500% of the volume of graphene is added to the reactor, and then a dehumidifier accounting for 2% of the mass of the graphene is added. After mixing evenly, the graphene is added, and the mixture is stirred at a low speed of 150 r / min for 30 minutes, and then stirred and refluxed at 60° C. for 6 hours. After the stirring is completed, the mixture is naturally cooled to room temperature, and the modified graphene is obtained by freeze drying.
[0167] Preparation of corrosion-inhibiting sealant:
[0168] First, wash the double planetary stirred tank with deionized water, dry it at 105°C for 12 h, and then fill it with clean dry nitrogen to replace the air in the double planetary stirred tank three times;
[0169] Add silane-modified polymer resin, non-alcohol plasticizer, nano calcium carbonate, carbon black, and hydrophobic fumed silica into a double planetary stirring kettle, and then stir for 90 minutes, wherein the stirring temperature is 110° C., the vacuum degree is -0.1 MPa, and the stirring speed is 1000 r / min;
[0170] The material temperature in the double planetary stirring kettle was cooled to below 40°C, a dehumidifier was added first, and the mixture was dispersed at a speed of 800 r / min for 20 min, and then flake zinc powder, modified graphene, and modified flake zinc powder were added, and the mixture was stirred for 60 min at a vacuum degree of -0.1 MPa and a speed of 1000 r / min; then an adhesion promoter was added, and the mixture was stirred at a speed of 1000 r / min for 20 min, and then a catalyst was added, and the mixture was stirred for 30 min at a vacuum degree of -0.1 MPa and a speed of 1000 r / min;
[0171] Clean dry nitrogen is used to adjust the pressure in the double planetary stirring kettle to normal pressure, and finally the materials are discharged and sealed to prepare the corrosion-inhibiting sealant.
[0172] According to the above data, the corrosion-inhibiting sealing paste, corrosion-inhibiting sealant and corrosion-inhibiting sealant prepared by the present invention all have excellent corrosion resistance, and therefore can help the high-speed railway sound barrier to build a more complete corrosion-resistant system.
[0173] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A corrosion-resistant treatment method for a high-speed railway sound barrier, characterized in that: The following steps are involved: S1. Preparation of modified flake zinc powder: S1.
1. Replace the gas in the ball mill with nitrogen for 3 times, first add toluene 10 to 20 times the volume of the flake zinc powder, then add the flake zinc powder, first stir at a low speed of 100 to 150 r / min for 5 to 10 minutes, after pre-dispersion, maintain the speed at 200 to 500 r / min and the temperature at 30 to 40°C, perform ball milling for 4 to 12 hours, disperse the flake zinc powder evenly, then add a dehumidifier of 3 to 10% by mass of the flake zinc powder, maintain the ball milling dispersion conditions and continue the ball milling treatment for 1 to 4 hours; then add an adhesion promoter of 3 to 10% by mass of the flake zinc powder, maintain the conditions for ball milling treatment for 1 to 4 hours, and freeze-dry at -60 to -80°C for 40 hours to obtain the pretreated flake zinc powder; S1.2, using a new clean and dry ball mill and replacing the air with clean nitrogen, add 5 to 10 times the volume of the pre-treated flake zinc powder toluene solvent, then add 5 to 10% of the mass of the toluene solution of polyamide wax powder, stir at a low speed of 100 to 150 r / min until the polyamide wax powder is completely dissolved, then add the pre-treated flake zinc powder, the temperature is 30 to 40 ° C, the speed of 200 to 500 r / min ball milling treatment for 2 to 3 hours, and freeze-dry at -60 to -80 ° C for 40 hours to obtain the modified flake zinc powder; S2. Preparation of modified graphene: S2.1, add ethyl acetate solution with a total volume of 300-500% of the volume of graphene into the reactor, then add a dehumidifier accounting for 1-2% of the mass of graphene, add graphene after mixing evenly, stir at a low speed of 100-150r / min for 5-30min, then stir and reflux at 50-60°C for 4-6h, cool naturally to room temperature after stirring, and freeze-dry at -60--80°C for 24-40h to obtain pretreated graphene; S2.2, under nitrogen protection, acrylamide and methacryloyloxyethyl trimethyl ammonium chloride, 4-chloromethyl styrene and ammonium persulfate in a molar ratio of 10:3:0.02:0.005 are mixed, the temperature is raised to 55-65°C, and stirred for 10-14 hours. After the stirring is completed, anhydrous ethanol is added for extraction, and freeze-dried at -60--80°C for 24 hours to obtain a cationic polyacrylamide prepolymer; S2.3, adding cationic polyacrylamide prepolymer and enzymatic lignin in a mass ratio of (1-3):1 to a sodium hydroxide solution with a concentration of 1 mol / L, stirring at 60-80°C for 5 h, cooling to room temperature after stirring, extracting with acetone, discarding the upper liquid, filtering the remaining solid product, concentrating, and freeze-drying at -60°C for 24 h to obtain pure lignin-based cationic polyacrylamide; S2.4, 40 to 60 parts of a 1 to 1.5 g / L lignin-based cationic polyacrylamide aqueous solution and 15 to 25 parts of pretreated graphene are uniformly mixed, spray-dried at 60 to 90° C., and then ground in a ball mill at a speed of 350 r / min for 4 h to prepare the modified graphene; S3, preparing corrosion-inhibiting sealing paste, corrosion-inhibiting sealant and corrosion-inhibiting sealant; S4. Pretreatment of high-speed rail sound barrier: Before installing the high-speed rail sound barrier, clean the upper surface of the embedded parts and the surrounding concrete surface, bolts and exposed surfaces, and then apply special primer to protect the substrate from waterproofing and seepage; S5, corrosion-inhibiting sealing paste treatment: Apply corrosion-inhibiting sealant between the support base plate and the base concrete, on the bolts, the surface of the support screw holes, and the inner surface of the nuts, fix the bolts in the support screw holes, then screw on the nuts and place the support to ensure that the space between the support base plate and the base concrete is filled with corrosion-inhibiting sealant so that there is no gap between the support base plate and the base concrete; S6, corrosion-inhibiting sealant treatment: Tighten the nuts of the connecting bolts to the required standard, remove the corrosion-inhibiting sealant remaining on the edge of the joints between the exposed bolts, the support base plate and the concrete foundation, and then apply a layer of corrosion-inhibiting sealant on the surface of the exposed bolts; S7, corrosion-inhibiting sealant treatment: A layer of corrosion-inhibiting sealant is scraped on the edge of the joint between the base plate and the concrete of the foundation to ensure a smooth slope at the joint. After it is completely dried, a corrosion-resistant high-speed rail sound barrier will be obtained.
2. The corrosion resistance treatment method for high-speed railway sound barrier according to claim 1 is characterized in that: In step S1 and step S2, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21.
3. The corrosion-resistant treatment method for high-speed railway sound barrier according to claim 1 is characterized in that: In step S1, the adhesion promoter is one of Meitu A-1120 and domestic WD51.
4. The corrosion-resistant treatment method for high-speed railway sound barrier according to claim 1 is characterized in that: In step S3, the preparation process of the corrosion-inhibiting sealing paste is as follows: S4.
1. First, wash the double planetary stirring kettle with deionized water, dry it at 100-105°C for 8-12h, and then introduce nitrogen for 50-80min. Then, add 20-40 parts of MS S327-silane modified polyether resin, 10-28 parts of non-alcoholic plasticizer, 5-10 parts of hydrophobic fumed silica and 0-20 parts of nano calcium carbonate in the stirring kettle in order by weight, and then stir for 45-60min, wherein the stirring temperature is 90-110°C, the vacuum degree is -0.09--0.1MPa, and the stirring speed is 800-1000r / min. S4.
2. Cool the material temperature in the double planetary stirred tank to below 40°C, add 1 to 2 parts of dehumidifier, stir at a speed of 500 to 600 r / min for 10 to 20 min, add 1 to 2 parts of adhesion promoter, stir at a speed of 400 to 600 r / min for 10 to 20 min, then add 15 to 30 parts of flake zinc powder, stir at a vacuum degree of -0.09 to -0.1 MPa and a stirring speed of 600 to 800 r / min for 20 to 45 min, then add 10 to 15 parts of modified flake zinc powder, keep stirring for 15 to 30 min while keeping the conditions unchanged; S4.
3. Finally, clean dry nitrogen is used to adjust the double planetary stirring kettle to normal pressure, and then the material is discharged and sealed to obtain the corrosion-inhibiting sealing paste.
5. The corrosion-resistant treatment method for high-speed railway sound barrier according to claim 1 is characterized in that: In step S3, the preparation process of the corrosion-inhibiting sealant is as follows: S5.
1. First wash the double planetary stirring kettle with deionized water, then dry it at 100-105℃ for 8-12h, and then fill it with clean dry nitrogen to replace the air in the double planetary stirring kettle 2-3 times; S5.2, add 20-30 parts of α-dimethoxysilane-terminated polyether resin, 10-20 parts of γ-trimethoxysilane-terminated polyether resin, 15-20 parts of non-alcohol plasticizer, 8-20 parts of hydrophobic fumed silica, 1-2 parts of carbon black, 5-30 parts of nano calcium carbonate in a double planetary stirred kettle, and then stir for 30-60 minutes, wherein the stirring temperature is 90-110°C, the vacuum degree is -0.09-0.1MPa, and the stirring speed is 800-1000r / min; S5.
3. Cool the material temperature in the double planetary stirred tank to below 40°C, first add 1 to 2 parts of dehumidifier, stir at a speed of 300 to 500 r / min for 5 to 10 minutes, continue to add 1 to 5 parts of modified graphene and 5 to 10 parts of modified flake zinc powder, stir for 10 to 30 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min; then add 1 to 2 parts of adhesion promoter, stir at a speed of 300 to 500 r / min for 5 to 10 minutes, then add 1 to 2 parts of catalyst, stir for 5 to 10 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min; S5.
4. Use clean dry nitrogen to adjust the double planetary stirring kettle to normal pressure, and finally discharge the materials and seal them to prepare the corrosion-inhibiting sealant.
6. The corrosion resistance treatment method for high-speed railway sound barrier according to claim 1 is characterized in that: In step S3, the preparation process of the corrosion-inhibiting sealant is as follows: S6.
1. First wash the double planetary stirring kettle with deionized water, then dry it at 100-105°C for 8-12 hours, and then fill it with clean dry nitrogen to replace the air in the double planetary stirring kettle 2-3 times; S6.2, add 20-30 parts of silane-modified polymer resin, 10-20 parts of non-alcohol plasticizer, 35-50 parts of nano calcium carbonate, 1-2 parts of carbon black, 0.5-2 parts of hydrophobic fumed silica into a double planetary stirred kettle, and then stir for 60-90 minutes, wherein the stirring temperature is 90-110°C, the vacuum degree is -0.09-0.1MPa, and the stirring speed is 800-1000r / min; S6.
3. Cool the material temperature in the double planetary stirred tank to below 40°C, first add 1 to 2 parts of dehumidifier, disperse at a speed of 500 to 800 r / min for 10 to 20 minutes, then add 2 to 5 parts of flake zinc powder, 1 to 5 parts of modified graphene, and 2 to 5 parts of modified flake zinc powder, and stir for 30 to 60 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min; then add 1 to 2 parts of adhesion promoter, stir at a speed of 800 to 1000 r / min for 10 to 20 minutes, then add 1 to 2 parts of catalyst, and stir for 20 to 30 minutes at a vacuum degree of -0.09 to -0.1 MPa and a speed of 800 to 1000 r / min; S6.
4. Use clean dry nitrogen to adjust the double planetary stirring kettle to normal pressure, and finally discharge the materials and seal them to prepare the corrosion-inhibiting sealant.
7. The corrosion-resistant treatment method for high-speed railway sound barrier according to claim 4 is characterized in that: In step S4.1, the non-alcohol plasticizer is one of diisononyl phthalate, dioctyl phthalate and diisodecyl phthalate; in step S4.2, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21, and the adhesion promoter is one of Meitu A-1120 and domestic WD51.
8. The corrosion-resistant treatment method for high-speed railway sound barrier according to claim 5 is characterized in that: In step S5.2, the non-alcohol plasticizer is one of diisononyl phthalate, dioctyl phthalate and diisodecyl phthalate; in step S5.3, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21, the adhesion promoter is one of Meitu A-1120 and domestic WD51, and the catalyst is one of stannous octoate and dibutyltin dilaurate.
9. The corrosion-resistant treatment method for high-speed railway sound barrier according to claim 6, characterized in that: In step S6.2, the non-alcohol plasticizer is one of diisononyl phthalate, dioctyl phthalate and diisodecyl phthalate; in step S6.3, the dehumidifier is one of Maitu A-171, A-1630A, and domestic WD21, and the adhesion promoter is one of Meitu A-1120 and domestic WD51.
10. The corrosion resistance treatment method for high-speed railway sound barrier according to claim 6, characterized in that: In step S6.3, the catalyst is one of stannous octoate and dibutyltin dilaurate.